Oligomeric Bax Is a Component of the Putative Cytochrome c Release Channel MAC, Mitochondrial Apoptosis-induced Channel - Dejean, Laurent M. (The American Society for Cell Biology, 2005)
Bcl-2 family proteins regulate apoptosis, in part, by controlling formation of the mitochondrial apoptosis-induced channel (MAC), which is a putative cytochrome c release channel induced early in the intrinsic apoptotic pathway. This channel activity was never observed in Bcl-2–overexpressing cells. Furthermore, MAC appears when Bax translocates to mitochondria and cytochrome c is released in cells dying by intrinsic apoptosis. Bax is a component of MAC of staurosporine-treated HeLa cells because MAC activity is immunodepleted by Bax antibodies. MAC is preferentially associated with oligomeric, not monomeric, Bax. The single channel behavior of recombinant oligomeric Bax and MAC is similar. Both channel activities are modified by cytochrome c, consistent with entrance of this protein into the pore. The mean conductance of patches of mitochondria isolated after green fluorescent protein-Bax translocation is significantly higher than those from untreated cells, consistent with onset of MAC activity. In contrast, the mean conductance of patches of mitochondria indicates MAC activity is present in apoptotic cells deficient in Bax but absent in apoptotic cells deficient in both Bax and Bak. These findings indicate Bax is a component of MAC in staurosporine-treated HeLa cells and suggest Bax and Bak are functionally redundant as components of MAC.